Introducing Japanese popular culture - Freedman, Alisa; Slade, Toby (Routledge, 2018)
"Specifically designed for use on a range of undergraduate and graduate courses, Introducing Japanese Popular Culture is a comprehensive textbook offering an up-to-date overview of a wide variety of media forms. It uses particular case studies as a way into examining the broader themes in Japanese culture and provides a thorough analysis of the historical and contemporary trends that have shaped artistic production, as well as, politics, society, and economics in Japan. As a result, more than being a time capsule of influential trends, this book teaches enduring lessons about how popular culture reflects the societies that produce and consume it. With contributions from an international team of scholars, representing a range of disciplines from history and anthropology to art history and media studies, the book's sections include: Television, Videogames, Music, Popular Cinema, Anime, Manga, Popular Literature, Fashion, Contemporary Art. Written in an accessible style by a stellar line-up of international contributors, this textbook will be essential reading for students of Japanese culture and society, Asian media and popular culture and Asian Studies in general."--Provided by publisher.